Issues of realization of the general principles of accountability in national legal system of the Republic of Kazakhstan - Ualieva, Zh. (KSU publ, 2015)
In the presented article issues of a role of the conventional principles of international law in system of the national right of the Republic of Kazakhstan are considered, the characteristic of their contents and feature is given. The carried-out comparative analysis of criminal and legal, administrative precepts of law which consolidated the general principles of responsibility, new approaches to research of this problem gave the chance in to formulate to authors conclusions and regulations on this topical issue.
Keywords: international law; international treaties; national law; sources of law; implementation; implement; the principle of the supremacy of the Constitution; the primacy of international standards